2021
DOI: 10.1002/jmv.27273
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the efficacy of extracted squalene from seed oil in the form of microemulsion for the treatment of COVID‐19: A clinical study

Abstract: This study investigates the effect of the nanostructure of squalene in the form of microemulsion on COVID‐19 patients. In this blinded clinical trial, a comparison was made between the efficacy of squalene treatment and controls. A total of 30 COVID‐19 patients admitted to the emergency department, and the infection ward was equally allocated to case ( n = 15) and control ( n = 15) groups according to their age and underlying diseases. The baseline characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…37 A recent report revealed that intravenous squalene BID could significantly improve COVID-19 conditions without any adverse effect. 38,39 Taken altogether, the foregoing phytocompounds contained in TCEA 6.3 had a potential to act as anti-cancer and anti-retroviral agent.…”
Section: Discussionmentioning
confidence: 99%
“…37 A recent report revealed that intravenous squalene BID could significantly improve COVID-19 conditions without any adverse effect. 38,39 Taken altogether, the foregoing phytocompounds contained in TCEA 6.3 had a potential to act as anti-cancer and anti-retroviral agent.…”
Section: Discussionmentioning
confidence: 99%
“…Then, it was assessed in the form of a nanostructure in a clinical study to treat COVID-19. It showed marked properties by reducing fever and cough during the treatment period and the treated patients did not need oxygen therapy [ 79 ].…”
Section: Medicinal Plants and Their Metabolites Used In Case Of Covid-19mentioning
confidence: 99%
“…Squalene also has anti-oxidative properties and used as adjuvant in vaccines and cosmetics ( Fox, 2009 ). Squalene in microemulsions has been shown to be antimicrobial against MRSA ( Fang et al., 2019 ), and effective in the treatment of COVID-19 patients ( Ebrahimi et al., 2022 ).…”
Section: Antimicrobial Potential Of Lipid Classes In Tearsmentioning
confidence: 99%